Flexible, wearable, and stretchable electronics - Sakuma, Katsuyuki (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"In this book, we provide a comprehensive technological review on the most state-of-the art developments in FWS electronics. This book provides the reader a taste of what is possible with FWS electronics and how these electronics can provide unique solutions for a wide variety of applications. Furthermore, the book introduces and explains new applications of flexible technology that has opened up the future potential of FWS electronics"--
OCLC-licensed vendor bibliographic record.
Keywords: Flexible electronics; Wearable technology; COMPUTERS / Computer Engineering; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General